2015
DOI: 10.1007/s10725-015-0116-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-insensitive mutants of Nicotiana tabacum exhibit drought stress resistance

Abstract: Drought is one of the major environmental stresses that profoundly affect crop growth and yield. The gaseous hormone ethylene is believed to be critical for plant growth and drought tolerance. Based on the darkgrown seedling response to ethylene, a genetic screen for tobacco (Nicotiana tabacum) mutants on medium supplemented with ACC (1-aminocyclopropane-1-carboxylic acid), the precursor of ethylene, was performed. Among the ethylene insensitive mutants that were isolated, drought resistant mutants were subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Ethylene also functions in plant responses to salt stress. For example, the Arabidopsis ethylene insensitive mutants ethylene response1-1 (etr1-1), etr2-1, ethylene insensitive2-1 (ein2-1), ein2-5, ein3-1, and ein4-1 showed reduced salt tolerance [22][23][24], while the tobacco and wheat mutants with reduced ethylene sensitivity exhibited increased salt resistance [25,26]. It was reported that ethylene was important for salt responses of Arabidopsis, grapevines, maize, and tomato, and ethyleneregulated salt responses in plants mainly by maintaining the homeostasis of Na + /K + ratio, nutrients, and ROS, and the assimilation of nitrates and sulfates [27].…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene also functions in plant responses to salt stress. For example, the Arabidopsis ethylene insensitive mutants ethylene response1-1 (etr1-1), etr2-1, ethylene insensitive2-1 (ein2-1), ein2-5, ein3-1, and ein4-1 showed reduced salt tolerance [22][23][24], while the tobacco and wheat mutants with reduced ethylene sensitivity exhibited increased salt resistance [25,26]. It was reported that ethylene was important for salt responses of Arabidopsis, grapevines, maize, and tomato, and ethyleneregulated salt responses in plants mainly by maintaining the homeostasis of Na + /K + ratio, nutrients, and ROS, and the assimilation of nitrates and sulfates [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tobacco (Nicotiana tabacum) seedlings treated with ACC had decreased levels of MDA and hydrogen peroxide (H 2 O 2 ), while a restored activity of peroxidase (POX) and superoxide dismutase (SOD) under drought stress (Wang et al, 2016; Table 1). Moreover, ethephon-treated (300-500 ppm) maize plants had increased leaf number, total pigments, chlorophyll content, rate of transpiration, free proline and grain yields under drought stress (Abdel-Ati et al, 2007).…”
Section: Oxidative Stress Metabolism and Defense Systemsmentioning
confidence: 99%
“…This is achieved by regulating cuticular wax production, which plays a crucial role in sustaining water levels and membrane stability necessary for plant growth (Yu et al, 2017a). In addition, ethylene biosynthesis precursor, 1‐aminocyclopropane‐1‐carboxylic acid (ACC), has been extensively studied for its ability to enhance drought tolerance in plants (Valluru et al, 2016; Wang et al, 2016). Ethylene signaling plays a crucial role in ameliorating drought‐triggered obstacles on plants by regulating various physiological and metabolic processes, including maintaining the equilibrium between oxidative stress management and antioxidant systems (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, transgenic tobacco plants with reduced ethylene biosynthesis showed elevated salinity tolerance (Riyazuddin et al, 2020; Tavladoraki et al, 2012), while an exogenous ethylene treatment in rice led to salinity hypersensitivity (Yang et al, 2015). Similarly, Wang et al (2016) reported that ethylene‐insensitive tobacco mutants exhibited enhanced drought resistance, with a lower leaf water loss due to a smaller stomatal aperture, increased peroxidase and superoxide dismutase activities, and a higher accumulation of proline (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, Wang et al (2016) reported that ethylene-insensitive tobacco mutants exhibited enhanced drought resistance, with a lower leaf water loss due to a smaller stomatal aperture, increased peroxidase and superoxide dismutase activities, and a higher accumulation of proline (Wang et al, 2016).…”
mentioning
confidence: 94%